2018
DOI: 10.1016/j.electacta.2018.03.135
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pt and Ag nanoparticles composites with polyphenazines onto ITO electrodes during the oxidation of H2O2 with ascorbic acid

Abstract: Six polyphenazine electrodes modified with platinum and silver nanoparticles deposited over conducting polymers have been prepared using electrochemical techniques. Phenazine monomers were electropolymerized on Indium tin oxide (ITO) and their morphology was explored by SEM-EDX and Raman spectroscopy. The main findings indicated that the polymers are not homogenously electrodeposited, having pores where metal nanoparticles can be nested, which can play an important role in the ionic exchange with the electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Figure 2(c and d) indicates the distribution of the platinum nanoparticles on the surface of the Poly(Isoleucine) film with size range from 30 nm to 100 nm. Crystallite aggregation of platinum nanoparticles forming bright flower‐like structures increased the porosity and roughness of the electrode as well as the electrochemical surface area [34]. The SEM images indicated that the platinum nanoparticles are effectively modified on Poly(Isoleucine) films.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2(c and d) indicates the distribution of the platinum nanoparticles on the surface of the Poly(Isoleucine) film with size range from 30 nm to 100 nm. Crystallite aggregation of platinum nanoparticles forming bright flower‐like structures increased the porosity and roughness of the electrode as well as the electrochemical surface area [34]. The SEM images indicated that the platinum nanoparticles are effectively modified on Poly(Isoleucine) films.…”
Section: Resultsmentioning
confidence: 99%